First observation of the radiative decay [lambda]0b→[lambda]γ - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2019)
The radiative decay Λ0b→Λγ is observed for the first time using a data sample of proton-proton collisions corresponding to an integrated luminosity of 1.7 fb−1 collected by the LHCb experiment at a center-of-mass energy of 13 TeV. Its branching fraction is measured exploiting the B0→K*0γ decay as a normalization mode and is found to be B(Λ0b→Λγ)=(7.1±1.5±0.6±0.7)×10−6, where the quoted uncertainties are statistical, systematic, and systematic from external inputs, respectively. This is the first observation of a radiative decay of a beauty baryon.
LHCb Collaboration, R. Aaij, S. Bachmann, D. Berninghoff, M. Borsato, S. Braun, A. Comerma-Montells, P. d’Argent, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, M. Heß, J. Hu, M. Kecke, M. Kolpin, R. Kopecna, B. Leverington, H. Malygina, J. Marks, D.S. Mitzel, S. Neubert, A. Piucci, M. Schmelling, N. Skidmore, M. Stahl, S. Stemmle, U. Uwer, H. Viemann, R. Waldi, A. Zhelezov [und viele weitere]
Im Titel ist beim erst genannten Lambda die Zahl "0" hochgestellt und "b" tiefgestellt
Gesehen am 29.04.2020